2020
DOI: 10.2147/jpr.s251782
|View full text |Cite
|
Sign up to set email alerts
|

<p>Altered BDNF Methylation in Patients with Chronic Musculoskeletal Pain and High Biopsychosocial Complexity</p>

Abstract: The INTERMED instrument, which was developed to measure patient's biopsychosocial (BPS) complexity, represents a powerful diagnostic and therapeutic tool. Epigenetic changes are the interface between signals from the environment and genetic modifications, affecting gene expression, in particular, by DNA methylation of CpG dinucleotides in promotor regions of the corresponding genes. The brain-derived neurotrophic factor (BDNF) gene plays a crucial role in the central sensitization (CS) of pain. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Uncertainty avoidance measures the extent to which a society is able to tolerate ambiguous or uncertain situations; high scores on this dimension imply that a country's culture would have rigid codes of conduct and be intolerant of unconventional ideas or behaviour ( 88 ). In a study of patients with chronic musculoskeletal pain, a measure of the complexity of each patient's psychosocial situation was found to be associated with altered methylation of the brain-derived neurotrophic factor (BDNF) gene ( 89 ). BDNF is an important regulator of neural plasticity, and plays a central role in several psychological processes related to chronic pain, including stress response, learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty avoidance measures the extent to which a society is able to tolerate ambiguous or uncertain situations; high scores on this dimension imply that a country's culture would have rigid codes of conduct and be intolerant of unconventional ideas or behaviour ( 88 ). In a study of patients with chronic musculoskeletal pain, a measure of the complexity of each patient's psychosocial situation was found to be associated with altered methylation of the brain-derived neurotrophic factor (BDNF) gene ( 89 ). BDNF is an important regulator of neural plasticity, and plays a central role in several psychological processes related to chronic pain, including stress response, learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…While genetic alterations offer a partial explanation for chronic pain, the emerging field of epigenetics provides a more nuanced and dynamic perspective by unraveling the gene expression patterns associated with chronic pain [154,155]. Recent studies revealed that epigenetic mechanisms, including histone acetylation [156], non-coding RNAs [156,157], and DNA methylation [127,158,159], can influence the expression of BDNF (Figure 2, Table 3). These epigenetic modifications may contribute to the pathogenesis and symptomatology of chronic pain.…”
Section: The Epigenetic Regulation Of Bdnf Expression In Chronic Painmentioning
confidence: 99%
“…Psychosocial factors also influence gene expression in chronic musculoskeletal pain: for example, higher levels of BDNF expression are related to higher biopsychosocial complexity and can be linked to an increased risk of central plasticity. 62 Other research suggests that different micro-ribonucleic acid (micro-RNA) fragments have higher expression in neuropathic versus nociceptive musculoskeletal pain. 63 …”
Section: Mood Demographic and Social Factorsmentioning
confidence: 99%
“…61 Psychosocial factors also influence gene expression in chronic musculoskeletal pain: for example, higher levels of BDNF expression are related to higher biopsychosocial complexity and can be linked to an increased risk of central plasticity. 62 Other research suggests that different micro-ribonucleic acid (micro-RNA) fragments have higher expression in neuropathic versus nociceptive musculoskeletal pain. 63 In summary, the assessment of and therapeutic development for chronic musculoskeletal pain must be global, focusing not only on molecular targets but also on demographic, psychological, and contributing social factors.…”
Section: Sex and Musculoskeletal Painmentioning
confidence: 99%